Transformational Leadership and Its Impact on Crisis Management: A Field Study in Yemeni Shipping Companies - Najeeb Mohammed Yahya Al-Beshari; Bushra Mohealdeen Ali Alshahari (University of Science and Technology, Sana’a, Yemen, 2024)
This study aimed to determine the level of crisis management and the level of practicing transformational leadership and its impact on crisis management in Yemeni shipping companies. To achieve the study objectives and test its hypotheses, the descriptive-analytical approach was used. A questionnaire was developed to collect primary data from a study population of (478) individuals. A study sample of (214) individuals was selected using the non-proportional stratified random sampling method. The data were statistically analyzed using the Statistical Package for the Social Sciences (SPSS). The study findings revealed that there is a statistically significant impact of transformational leadership on crisis management in Yemeni shipping companies and there is a statistically significant impact of the dimensions of transformational leadership (idealized influence, intellectual stimulation, and individual consideration) on crisis management in the companies. However, there was no statistically significant impact of the transformational leadership dimension (inspirational motivation) on crisis management in the companies. Additionally, the study found that the practice of crisis management and transformational leadership in Yemeni shipping companies was at a high level. The study recommends that Yemeni shipping companies should work effectively to enhance crisis management to overcome future challenges by adopting more advanced procedures and strategies to deal with crises in their early stages and prevent their occurrence. The study also recommends maintaining and continuously enhancing the achieved level of transformational leadership.